Behavioural Investigation On Table Tennis Blade Structure Using Finite Element Analysis - Muhamad Jais, Muhamad Amir Ezzat; Tajul Arifin, Ahmad Mubarak (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Table tennis is one of the sports that well known around the world. It is comprised of 2 players facing each other in single or 4 players facing each other in doubles. The table tennis was first regulated in 1926 by the International Table Tennis Federation (ITTF). Later on, table tennis is one of the recognized as an Olympic Sport in 1988. In this particular indoor sport, the most essential equipment is the table tennis blades. Table tennis has well known history of using the woods as its main equipment for utilizing the sport to its finest. The purpose of the study is to identify behavioural structure of kenaf natural fibre as the material of table tennis blade. The utilization of questionnaires for verification of characteristics behaviour on table tennis structure as well as input for simulations. The questionnaire resulting 62.5% out of 96 respondents strongly agree that weight of blade is affecting the playstyles in their game. In the future, the result from this study might be references for further study in kenaf natural fibre.